A message in poison [large type] - Magnani, Barbarajean (Magnani, Barbarajean. Dr. Lily Robinson, 2025)
"Sparks fly as Dr. Lily Robinson, the brilliant academic pathologist and covert assassin for the U.S. government, investigates two seemingly unrelated deaths alongside her lover, Agent Jean Paul Marchand, and Washington, D.C., Medical Examiner Dr. Logan Pelletier. A U.S. senator and the president of a developing nation are found dead in their beds. As governments thousands of miles apart react to the fallout and begin their investigations, no one claims responsibility, and no motives are clear. Yet, the cause of death implies a link between the two--one that only a mind versed in poisons and politics can decipher. With her personal relationships teetering on the brink and her loved ones facing foreign threats, Lily must unravel the mystery and uncover a plot more calculating than anyone could imagine--but it may be too late."--